The pineal complex in the cichlid Cichlasoma dimerus: effect of different photoperiods on its cell morphology. Issue 3 (27th June 2014) - Birba, A.; Ramallo, M. R.; Morandini, L.; Villafañe, V.; Tubert, C.; Guimarães Moreira, R.; Pandolfi, M.
<x xml:space="preserve">Abstract</x> This research describes the pineal complex histology in juvenile and adult Cichlasoma dimerus, and the effect of different photoperiods on its cell morphology. In both juveniles and adults, the pineal complex of C. dimerus has three components: the pineal organ, consisting of a pineal vesicle (PV) and a pineal stalk, the parapineal organ and the dorsal sac. Although a strong morphological resemblance exists between the two stages, different synthesis patterns of cone and rod opsins were detected in the two life stages. An effect of the photoperiod length was observed on putative pinealocytes' activity from the PV, measured indirectly through nuclear area morphometry. Individuals exposed to a natural photoperiod (14L:10D) had smaller nuclear areas (mean ± s.e. = 13·82 ± 1·52 µm2) than those exposed to a short photoperiod (8:16) (21·45 ± 2·67 µm2; P < 0·001). Eventually, the nuclear area of pinealocytes could be used as a putative indicator of melatonin synthesis in fishes where it is difficult to obtain plasma samples, e.g. due to its small size or age. This work constitutes one of the few comparative descriptions of the pineal complex of juvenile and adult teleost and suggests potential approaches for the study of melatonin synthesis in fish larvae or small adult fishes.